THE EFFECT OF NORMATIVE COMMITMENT AND PERSON-JOB FIT ON EMPLOYEE PERFORMANCE OF PT. TOTUM DIBA CIREBON - Putri Nur Sulistia Hidayat; Dedi Muhammad Siddiq; Lisa Harry Sulistiyowati; Yunita Maudi Ruswandi (Universitas Muhammadiyah Kendari, 2023)
The aim of this study is to investigate the impact of normative commitment and person-job-fit on the performance of employees in the production department at PT. Totum Diba Cirebon. The study's population consists of employees working in the production department of PT. Totum Diba Cirebon. The researchers utilized probability sampling through simple random sampling technique to select 117 respondents, randomly chosen from the population using Slovin's formula. Data was collected through a questionnaire, and the data analysis method employed was multiple linear regression analysis. The results revealed a positive and significant influence of the normative commitment variable on employee performance, with a t-count > t-table (4.402 > 1.528) and a significance value of 0.000 < 0.05. Additionally, Person-Job-Fit showed a positive and significant impact on employee performance, with a t-count > t-table (3.301 > 1.528) and a significance value of 0.001 < 0.05. Furthermore, both normative commitment and person-job-fit had a clearly positive effect on employee performance, as demonstrated by F-count > F-table (18.179 > 3.08) and a significance value of 0.000 < 0.05.